HUBUNGAN LITERASI DIGITAL DENGAN KETERAMPILAN BERPIKIR KREATIF MURID PADA PEMBELAJARAN BIOLOGI DI SMA NEGERI 12 PADANG - Herdayanti, Een; Helendra, Helendra; Yogica, Relsas; Olvia Rahmi, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The 21st century is characterized by rapid advancements across all sectors, particularly in education. 21st-century learning relies on technology as a medium to foster essential learning skills—specifically, digital literacy and creative thinking. Mastering these skills is crucial for navigating the challenges of the digital era. This study aims to determine whether a relationship exists between digital literacy proficiency and creative thinking skills among students in the biology course at SMA Negeri 12 Padang. Employing a descriptive research design with a quantitative approach, the study involved a sample of 175 respondents selected via purposive sampling. Data collection utilized a digital literacy questionnaire and an essay-based assessment of creative thinking skills, while data analysis was conducted using quantitative descriptive methods. The results indicate that both digital literacy and creative thinking skills among the students fall into the